The Influence of Instructional Leadership and School Culture Through Self-Efficacy on Senior High School Teacher Performance - Nisa, Devie Tiara; Rokhman, Fathur; Handoyo, Eko (Educational Management, 2025)
This study examines the impact of principals’ instructional leadership and school culture on teacher performance, with teacher self-efficacy as a mediating variable. Using a quantitative approach, data were collected from senior high school teachers in Brebes District via validated questionnaires and analyzed through path analysis. Results show that instructional leadership (β = 0.542) and self-efficacy (β = 0.383) significantly affect teacher performance, while school culture has a weaker direct effect (β = 0.027). Both instructional leadership (β = 0.332) and school culture (β = 0.543) significantly influence self-efficacy. The Sobel test confirms that self-efficacy mediates the effects of instructional leadership (Sobel = 4.614; p = 0.003) and school culture (Sobel = 5.629; p = 0.001) on performance. The study highlights the importance of strong instructional leadership and a positive school culture in enhancing teacher self-efficacy and performance. It recommends principals to reinforce leadership practices and promote supportive school environments. Future studies should explore broader contexts and include variables such as motivation or job satisfaction.